Entomological surveillance for rodent and their ectoparasites with special reference to potential of Scrub Typhus at Kolkata Port Trust (KPT), Kolkata (India) - Sharma, Abhay Kumar; Kumar, Kaushal (Archives of Advances in Biosciences, 2014)
Rodents are well established at port areas and their ectoparasite can be vectors of many diseases. Ships at seaport play an important role in spreading disease by transporting infected vectors. Plague, murine typhus, salmonellosis, trichinosis, leptospirosis and rat bite fever are known to be spread by rats. In view of the seriousness of the problem present study was undertaken to assess the prevalence of rodent – ectoparasite association at Kolkata Port Trust, Kolkata (India). A total of 442 rodent traps were laid and 17 rodents including two species of rodents Bandicota indica and Rattus rattus were collected with 3.8 trap positivity rate. Infestation rate of ectoprasites was 76.5%. Mites with 86.6% were the predominant ectoparisite retrieved from rodents followed by fleas and lice. The rodent ectoparasite index was 13.6 per rat. A total 78 vector larval trombiculide mite chigger (Leptotrombidium deliense) and 123 mesostigmatid mites (Laelaps sp.) were collected. Chigger infestation rate was found to be 11.1 per rat. Passenger terminal was the only site where no mite could be retrieved. A total 26 fleas were retrieved giving an overall flea index as 1.53. The flea species collected from rodents were Xenopsylla cheopis and Ctenocephalides felis. Serological examination of rodent serum was found non- reactive for Orentia (Scrub typhus) and plague antibodies. Bacteriological investigation of organs impression smear and tissue of rodents showed no plague bacilli activity and isolation of Yersinia pestis. Result of the study suggests routine surveillance for rodent and their arthropods ectoparasite to apply appropriate control methods for controlling transmission and spreading of rodent borne diseases.